Interference With ACSL1 Gene in Bovine Adipocytes: Transcriptome Profiling of mRNA and lncRNA Related to Unsaturated Fatty Acid Synthesis - Bai, Yanbin; Li, Xupeng; Chen, Zongchang; Li, Jingsheng; Tian, Hongshan; Ma, Yong; Raza, Sayed Haidar Abbas; Shi, Bingang; Han, Xiangmin; Luo, Yuzhu; Hu, Jiang; Wang, Jiqing; et al. (Frontiers in Veterinary Science, 2021)
The enzyme long-chain acyl-CoA synthetase 1 (ACSL1) is essential for lipid metabolism. The ACSL1 gene controls unsaturated fatty acid (UFA) synthesis as well as the formation of lipid droplets in bovine adipocytes. Here, we used RNA-Seq to determine lncRNA and mRNA that regulate UFA synthesis in bovine adipocytes using RNA interference and noninterference with ACSL1. The corresponding target genes of differentially expressed (DE) lncRNAs and the DE mRNAs were found to be enriched in lipid and FA metabolism-related pathways, according to GO and KEGG analyses. The differentially expressed lncRNA- differentially expressed mRNA (DEL-DEM) interaction network indicated that some DELs, such as TCONS_00069661, TCONS_00040771, TCONS_ 00035606, TCONS_00048301, TCONS_001309018, and TCONS_00122946, were critical for UFA synthesis. These findings assist our understanding of the regulation of UFA synthesis by lncRNAs and mRNAs in bovine adipocytes.